1985
DOI: 10.1029/ja090ia11p11087
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact excitation of atomic oxygen: Revised cross sections

Abstract: Revised cross‐section values for the excitation of the O I(3s ³S°‐2p ³P; λ1304 Å), O I(3d ³D°‐2p ³P; λ1027 Å), and O I(3s′ ³D°‐2p ³P; λ989 Å) resonance transitions by electron impact on atomic oxygen are presented from threshold to 300 eV. These results are smaller than the excitation cross sections used in some airglow models by a factor of ∼2.8. The revised values are in good agreement with recent quantum‐scattering calculations. The downward revision is required by new laboratory studies in which the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
61
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 45 publications
16
61
2
Order By: Relevance
“…The recommendation of Laher and Gilmore (1990) for process (a), deduced from calculations, is in qualitative agreement with the laboratory measurements reported by Stone and Zipf (1974), later corrected by Zipf and Erdman (1985) and Doering and Gulcicek (1989); the uncertainty reaches 50 %. At 70 eV energy, process (b) is around 50 times less efficient than process (a).…”
Section: Ionospheric Response: Modelling the Optical Emissionssupporting
confidence: 74%
“…The recommendation of Laher and Gilmore (1990) for process (a), deduced from calculations, is in qualitative agreement with the laboratory measurements reported by Stone and Zipf (1974), later corrected by Zipf and Erdman (1985) and Doering and Gulcicek (1989); the uncertainty reaches 50 %. At 70 eV energy, process (b) is around 50 times less efficient than process (a).…”
Section: Ionospheric Response: Modelling the Optical Emissionssupporting
confidence: 74%
“…They found that the incorporation of partial frequency redistribution also enhanced the predicted limb brightening. Their model calculations reproduced the measurements if the O densities from the BNMS model were reduced by about 40~o, but their analysis was based on cross sections for electron impact production of emission at 1304 and 1356 ~_ reported by Stone and Zipf (1974) that were later reduced by a factor of 2.8 (Zipf and Erdman, 1985;Zipf, 1986). A model of the terrestrial dayglow oxygen emissions (Meier et al, 1985) suggested that the Stone and Zipf cross sections should be scaled down by 40~o.…”
Section: Species Sourcementioning
confidence: 75%
“…The analysis of Rottman and Moos was based on the Venus model of Strickland (1973), except for the cross sections for electron impact excitation of O, which were adopted from Zipf and Stone (1971). These cross sections have recently been shown to be too large, by a factor of about 7 for the 1304 A emission and a factor of 2 for the 1356 A emission (Stone and Zipf, 1974;Zipf and Erdman, 1985;Zipf, 1986). Rottman and Moos found electron impact excitation to be the major source of both of the emissions.…”
Section: The Sources Of Dayglow Emission Features Include Photoionizamentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute excitation cross sections for the resonance lines at 1304, 1027, 989, and 878 Å are also reported by Kanik et al (2001) at 30, 50, and 100 eV using the electron-energy-loss method with uncertainties similar to the recent measurements of the Doering & Yang (2001). Emission cross sections for the 1304 Å line are measured by Noren et al (2001), while the measured emission cross sections for the lines at 1304, 1027, 989, and 878 Å are presented by Wang & McKonckey (1992), Zipf & Erdman (1985), and Zipf & Kao (1986).…”
Section: Introductionmentioning
confidence: 99%